Comparison the efficacy of honey mouthwash with hydrogen peroxide mouthwash on oral lesions healing in patients with Pemphigus .Abstract Background Pemphigus is a rare and potentially life-threatening disease. It produces blisters in the skin and mucous m - Parvin, Mahshid; Ashktorab, Tahereh; Dabirian, Azam; Nassiri Oskuee, Navideh (Advances in Nursing & Midwifery, 2012)
Abstract Background Pemphigus is a rare and potentially life-threatening disease. It produces blisters in the skin and mucous membranes. In more than 81% of cases, pemphigus involves oral mucosa. This study assessed the efficacy of mouthwash with honey compared with hydrogen peroxide on oral lesions healing in Pemphigus patients. Materials and methods A randomized design clinical trial was carried on 49 patients with oral pemphigus lesions. Patients randomly divided into experimental and control groups. Patients were assessed for 10 days. Data were collected by questionnaire, Oral Mucositis Visual Assessment Guide of WHO, visual analog scale of pain intensity and time Diaries. Results Age, sex, educational level, marital status, history of crisis in the past 6 months, history of autoimmune disease and history of pemphigus disease in their family, were not statistically significant differente in experimental (honey mouthwash) and control (hydrogen peroxide mouthwash) groups. Degree of oral lesions faster was improved in experimental (honey mouthwash) group compared with control (hydrogen peroxide mouthwash) group. Reducing pain intensity in the experimental group was significant from the third day(P = 0.001), while it was not statistically significant in the control group until the tenth day of assessment. Conclusion Honey mouthwash compared with hydrogen peroxide has had faster effect on oral lesions healing and more effective on reducing pain in pemphigus patients. Honey mouthwash has no complication in this group of patients. Key words: pemphigus, oral lesions, honey, Hydrogen peroxide